PENGARUH MODEL TAKE AND GIVE DAN MODEL KONVENSIONAL TERHADAP KEMAMPUAN MENGANALISIS TEKS RESENSI - Fauziah, Inti Fadah; Mering, Aloysius; Saman, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe study aims to determine the influence of take and give learning models on the ability to analyse reviewer text. The specific purpose of this research is: 1) Knowing the difference of learning outcomes among learners who are taught with take and give models and conventional models in analyzing the text of reviews; 2) Knowing the differences between learners who get high scores and who get low scores in learning using take and give models and conventional models in analyzing reviewer text; 3) Knowing the presence or absence of interactions between the model of learning and student learning outcomes on the ability to analyze the reviewer's text; 4) know the difference in high learning outcomes analyzing the reviewer text between learners taught with take and give models and being taught with conventional models, and 5) Knowing low learning outcomes analyses the reviewer text between learners who are taught with take and give models and conventional models. This research uses factorial design methods. The sample are student?s of XI SMA Islam Bawari. The results showed that there were differences ability to analyze the reviewer text that was given treatment between take and give models with conventional models with Fcalculate>Ftabel of 22.78>4.00. Keywords: Analyzing The Text of Reviews, Conventional Models, Take and Give Models